Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Spatio-temporal human snow leopard (Panthera uncia) conflicts and mitigation measures in Baltistan - free-livestock grazing pastoral areas - Muhammad Zaman; Rodney Jackson; Shafqat Hussain (Journal for Nature Conservation, 2024)

Occurrence of Eutypella species on cotton (Gossypium hirsutum L.) in New South Wales, Australia - Duy Phu Le; Aphrika Gregson; Anna Madden; Rodney Jackson (Journal of Plant Pathology, 2023)
We report for the first time the occurrence of an Eutypella species on cotton in New South Wales (NSW), Australia. The putative Eutypella was isolated from dead cotton plants that exhibited atypical symptoms of either Fusarium or Verticillium wilt. Dead plants had symptoms resembling lightning strike damage with blackened outer bark around the fifth node zone. Internal vascular discoloration was reddish grey and often occurred in V-shaped sections. Sequences of the internal transcribed spacer (ITS) revealed a 93.7–94.1% similarity to Eutypella scoparia , indicating that the NSW cotton isolates represented a putatively novel species within the Eutypella genus. Pathogenicity of the isolated Eutypella was assessed on cotton stem cuts and living plants inoculated with culture agar plugs. Typical black necroses on outer bark and reddish vascular discoloration were reinduced in both Eutypella -inoculated stem cuts and living plants. Subsequently, the same Eutypella pathogen was successfully recovered, thus fulfilling Koch’s postulates. The detection of Eutypella on NSW cotton is believed to be an independent event from a recently reported occurrence of Eutypella on Queensland cotton. The Queensland detection occurred in the same 2017/18 cropping season at approximately 730 km apart and was associated with distinct Eutypella isolates.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Identification of Berkeleyomyces rouxiae causing black root rot disease on cotton seedlings in New South Wales, Australia - Duy P. Le; Aphrika Gregson; Rodney Jackson (Journal of General Plant Pathology, 2022)

Regional Comparison of Snow Leopard (Panthera uncia) Diet using DNA Metabarcoding - Charlotte E. Hacker; Matthew Jevit; Shafqat Hussain; Ghulam Muhammad; Bariushaa Munkhtsog; Bayaraa Munkhtsog; Yuguang Zhang; Diqiang Li; Yanlin Liu; John D. Farrington; Farida Balbakova; Azat Alamanov; et al. (Biodiversity and Conservation, 2021)

TEF1 sequence-based diversity of Fusarium species recovered from collar rot diseased cotton seedlings in New South Wales, Australia - Duy P. Le; Thao T. Tran; Aphrika Gregson; Rodney Jackson (Australasian Plant Pathology, 2020)

Characterization of 9 microsatellites and primers in snow leopards and a species-specific PCR assay for identifying noninvasive samples - Jan E. Janecka; Rodney Jackson; Bariusha Munkhtsog; William J. Murphy (Conservation Genetics Resources, 2014)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

The effect of sleep deprivation on BOLD activity elicited by a divided attention task - Melinda L. Jackson; Matthew E. Hughes; Rodney J. Croft; Mark E. Howard; David Crewther; Gerard A. Kennedy; Katherine Owens; Rob J. Pierce; Fergal J. O’Donoghue; Patrick Johnston (Brain Imaging and Behavior, 2011)

Auranofin disrupts selenium metabolism in Clostridium difficile by forming a stable Au–Se adduct - Sarah Jackson-Rosario; Darin Cowart; Andrew Myers; Rebecca Tarrien; Rodney L. Levine; Robert A. Scott; William Thomas Self (JBIC Journal of Biological Inorganic Chemistry, 2009)

Men who consume vegetable oils rich in monounsaturated fat: their dietary patterns and risk of prostate cancer (New Zealand) - Alan E. Norrish; Rodney T. Jackson; Susan J. Sharpe; C. Murray Skeaff (Cancer Causes & Control, 2000)